(untitled) (Journal of Information Technologies in Education (ITE), 2007)
The technology of the automated pedagogical diagnostics is analysed. The testing strategy and marking algorithm is proposed. The software “Expert 3.02”, based on suggested methods, is designed. The methods of administrating of the database of the test tasks are proposed. The approbation of this methods in the educational process of the Kharkiv National Pedagogical University is carried out.